2009
DOI: 10.1590/s1415-54192009000400016
|View full text |Cite
|
Sign up to set email alerts
|

Variáveis relevantes no tratamento da má oclusão de Classe II

Abstract: Results of orthodontic Class II malocclusion treatment can be influenced by inherent characteristics such as patient age, malocclusion severity and degree of compliance, or even by factors regarding the orthodontist's subjective preference such as the treatment protocol. Basically, Class II treatment protocols involve nonextraction or extraction of two or four premolars. However, a greater treatment success rate can be expected with the extraction protocol of two maxillary premolars, regardless of the skeletal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
0
3
0
8
Order By: Relevance
“…Lower results were found by [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] . Caries and premature losses of primary molars result in a reduction in arch length of approximately 2 to 4mm per quadrant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower results were found by [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] . Caries and premature losses of primary molars result in a reduction in arch length of approximately 2 to 4mm per quadrant.…”
Section: Discussionmentioning
confidence: 99%
“…It is ranked as the third greatest oral health problem worldwide, being outranked by caries and periodontal disease 2 . In addition, it is of a multifactorial nature, with hereditary, congenital, functional, environmental, nutritional, socioeconomic and educational influences 3 . Deleterious habits, among them finger and pacifier sucking, are described in the literature as the main etiologic factors of malocclusion in the primary and mixed stages of dentition [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that for the same age and degree of severity, the protocol for Class II malocclusion treatment with extraction of the two maxillary premolars is more efficient than the treatment protocol without extractions. 8,9 Regarding stability, it is consensus that anterior open bite is ranked among the most challenging treatments and its end results have been shown to be less stable. However, it is believed that with the establishment of a correct overjet, over bite and muscular balance between the lips and tongue there will be no relapse of the malocclusion.…”
Section: Final Considerationsmentioning
confidence: 99%
“…Diante a padronização dos pontos cefalométricos desenvolveram-se pontos faciais que influenciam no diagnóstico e prognóstico de um perfil facial ideal, onde baseia-se nas referências faciais como: ângulo anterior do lábio superior, ângulo anterior do lábio inferior, assim como os pontos Pog' (Pogônio Mole), e Altura Facial Anterior Inferior (AFAI), tendo a linha vertical verdadeira como referência (ARNETT et al, 1999). Dentre as alterações dentárias, é possível afirmar, por exemplo, que más oclusões como Classe II ou III de Angle e pacientes com mordida profunda alteram diretamente o perfil facial dos pacientes envolvidos e o diagnóstico correto dessas más oclusões somadas aos avanços que surgiram ao longo do tempo na Odontologia servem de base até aos dias atuais para o tratamento ortodôntico e também para novos procedimentos incluindo a harmonização facial (JANSON et al, 2018).…”
Section: Introductionunclassified